Desempenho de meios filtrantes na remoção de partículas nanométricas de aerossóis - Feitosa, Natália dos Reis (Universidade Federal de São Carlos, 2009)
The interest of studies on the development of techniques for removal of particles in the nanosized scale was promoted by concern about air quality and human health, in addition to restrictions on the control of ultrafine particles, wich are more intransigent by environmental laws. Additionally, the increasing application of nanoparticles in various areas of science and technology has stimulated the development of studies on the subject. Amongst the several equipments capable to operate with efficiency on the particle removal, the fibrous filters are distinguished. Such filters are, in principle, capable to act in sub-micrometer scale, but there is little information about its performance in the nano-sized scale. In this work the performance of a polyester filter, of a HEPA cellulose filter, of a quartz microfiber filter and also of cylindrical filtering membrane, provided by Pam-Membranas Seletivas Ltda, were evaluated. The experimental system was able to simulate a contamination of nanometric particles in a stream of ultrapure air, with the aim of investigating the efficiency of filter media in the removal of nanoparticles. The test aerosol was constituted by NaCl polydisperse nanoparticles, ranging from 6.15 to 245.1 nm. The performance of the filter was evaluated through the analysis of the efficiency of removal of nanoparticles, for the counting of particles before and after to cross the filtering media, using the electric mobility technique. This procedure was performed using the TSI Scannig Mobility Particle Sizer (SMPS), model 3936, which provides the particles concentration, in size range. The results, in general, have showed that the filter media loses efficiency with the increasing filtration velocity and increasing particle size, in the ranged studied, indicating the typical behavior of difusional mechanism. The filtering membranes have showed better performance in the removal of particles unlike the others filters analysed there was no tendency to increase the penetration of particles with increasing the velocity of filtration or particle diameter.
Keywords: Filtração; Partículas nanométricas; Filtros fibrosos; Filtração por membranas; Eficiência de coleta; Mobilidade elétrica; Nanometer particles; Fibrous filters; Membranes filtration; Collection efficiency; Electric mobility; ENGENHARIAS::ENGENHARIA QUIMICA